2001
DOI: 10.1021/bc010026v
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biorecognition and Internalization of HPMA Copolymers Containing Multiple or Multivalent Carbohydrate Side-Chains by Human Hepatocarcinoma Cells

Abstract: N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers containing pendant saccharide moieties (galactosamine, lactose, and triantennary galactose) were synthesized. The relationship between the content of saccharide moieties and three-dimensional arrangement of galactose residues and their biorecognition and internalization by human hepatocarcinoma HepG2 cells was investigated. The results obtained clearly indicated preferential binding of the trivalent galactose and the lactose-containing copolymers to these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 50 publications
(86 reference statements)
3
49
0
Order By: Relevance
“…A basic study of the rate of internalization revealed that the targeted polymer was internalized at a rate almost 2 orders of magnitude faster than that of the nontargeted polymer P2 (Figure 4). It should be noted that the recent data by David et al (30) indicate that even more dramatic differences in uptake should be possible using polymer with higher amounts of trivalent galactose.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A basic study of the rate of internalization revealed that the targeted polymer was internalized at a rate almost 2 orders of magnitude faster than that of the nontargeted polymer P2 (Figure 4). It should be noted that the recent data by David et al (30) indicate that even more dramatic differences in uptake should be possible using polymer with higher amounts of trivalent galactose.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing the galactose content of the polymer was recently reported to increase the internalization of HPMA copolymer in Hep G2 cells (30). The targeted polymer P1 tested in this work contained 14 mol% of galactosecontaining monomers.…”
Section: Effect Of Galactose On the Rate Of Polymer Internalizationmentioning
confidence: 87%
See 1 more Smart Citation
“…By the end of the 30-min incubation, binding approached saturation with 41.77% of the initial radioactivity, indicating that the cancer cells-mediated endocytosis of targeted poly(HPMA)-porphyrin-DTPA-99m Tc tracer by H22 cells. [28] Interestingly, the maximal uptake of poly(HPMA)-DTPA-99m Tc (nontargeted binding) also reached 16.40% of the total conjugate added due to the EPR effect. As controls, DTPA-99m Tc lacking the porphyrin group and passive-targeted HPMA polymeric carrier did not show any significant cell association ( Figure 2) (2.98%).…”
Section: In Vitro Specific Targetingmentioning
confidence: 97%
“…the resulting azacitidine-containing polymers [30]. Herein, polymerizable galactose mono-ester VGA was chosen as the comonomer because the galactose moiety could be employed as a targeting ligand to mediate drug to liver parenchymal cells [31]. VGA could be easily obtained by the same method as the preparation of VAC [27].…”
Section: Synthesis and Characterization Of Azacitidine-conjugating Pomentioning
confidence: 99%